A porcine study of the area of heated tissue during hot‐balloon ablation: Implications for the clinical efficacy and safety. (11th January 2021) - Nakahara, Shiro; Wakamatsu, Yuji; Sato, Hirotsugu; Otsuka, Naoto; Fukuda, Reiko; Watanabe, Ryuta; Kurokawa, Sayaka; Ishikawa, Tetsuya; Takaoka, Motoki; Nagashima, Koichi; Kobayashi, Sayuki; Taguchi, Isao; et al.
Abstract: Introduction: Hot‐balloon ablation depends solely on thermal conduction, and myocardial tissue is ablated by only conductive heating from the balloon surface. Despite growing clinical evidence of the efficacy and safety of hot‐balloon ablation for atrial fibrillation (AF), the actual tissue temperature and the mechanism of heating during such ablation has not been clarified. To determine, by means of a porcine study, the temperatures of tissues targeted during hot‐balloon ablation of AF performed with hot‐balloon set temperatures of 73°C or 70°C, in accordance with the temperatures now used clinically. Methods: After a right thoracotomy, thermocouples with markers were implanted epicardially on the superior vena cava (SVC) and pulmonary veins (PVs) in six pigs. The tissue temperatures during hot‐balloon ablation (balloon set temperatures of 73°C and 70°C, 180 s/PV) were recorded, and the maximum tissue temperatures and fluoroscopically measured distance from the balloon surface to the target tissues were assessed. Results: Sixteen SVC‐ and 18 PV‐targeted energy deliveries were performed. Full‐thickness circumferential PV lesions were created with all hot‐balloon applications. A significant inverse relation was found between the recorded tissue temperatures and distance ( r = −.67; p < .001) from the balloon surface. No tissue temperature exceeded either of the balloon set temperatures. The best distance cutoff value for achieving lethal tissue temperatures more than 50°C was 3.6 mm. Conclusion: The hot‐balloon set temperature, energy delivery time, and tissue temperature data obtained in this porcine study supported the clinical efficacy and safety of the hot‐balloon ablation as currently practiced in patients with AF.